Studi Morfologi Kelenjar Aksesoris Kelamin Jantan Sapi Sumba Ongole (Bos indicus) - Togola, Angelica Noni; Amalo, Filphin A.; Maha, Inggrid T.; Gaina, Cynthia D. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Sumba Ongole cattle are one of the local types of cattle that are most commonly found in Indonesia. Bulls have accessory gland are ampulla, vesicular glands, prostate glands, and bulbourethral glands. The aim of this research is to determine the anatomical morphology and histology of male accessory glands in Sumba Ongole cattle. The research sample was six Sumba Ongole cattle that had been slaughtered at the East Sumba Regency Slaughterhouse. Macroscopic examination carried out tissue fixation in 10% formalin, tissue processing, and hematoxylin-eosin staining. The results of the research show that the male accessory glands in Sumba Ongole cattle have the ampullary gland, vesicular gland, prostate gland and bulbourethral gland.. Microscopically, each gland is covered by a capsule and has a secretory gland. The ampullary secretory glands are lined by cylindrical epithelium and have a serous type. The secretory glands of the vesicular glands are lined with cylindrical epithelium and have a seromucous type, the secretory glands of the prostate gland are lined with cuboidal epithelium and have a seromucous type, and the secretory glands of the bulbourethral glands are lined by cuboidal epithelium and have the mucous type.